A Case Report of Aggressive Angiomyxoma in the Buttock of a Female - Aiwen Le; Zhibin Zheng; Tong Wu (Clinical Case Reports)
ABSTRACT Aggressive angiomyxoma presents distinctive MRI features like “whirl sign” and “layering sign.” Laparoscopic combined with perianal incision can minimize bleeding and organ damage risks for pelvic‐extending tumors. Surgical excision with negative pressure drainage aids wound healing. Long‐term follow‐up is crucial to prevent recurrence.